Enhanced left superior parietal activation during successful speech production in patients with left dorsal striatal damage and error-prone neurotypical participants. (13th August 2022) - Geva, Sharon; Schneider, Letitia M; Khan, Shamima; Lorca-Puls, Diego L; Gajardo-Vidal, Andrea; ,; Hope, Thomas M H; Green, David W; Price, Cathy J
Abstract: Functional imaging studies of neurotypical adults report activation in the left putamen during speech production. The current study asked how stroke survivors with left putamen damage are able to produce correct spoken responses during a range of speech production tasks. Using functional magnetic resonance imaging, activation during correct speech production responses was assessed in 5 stroke patients with circumscribed left dorsal striatal lesions, 66 stroke patient controls who did not have focal left dorsal striatal lesions, and 54 neurotypical adults. As a group, patients with left dorsal striatal damage (our patients of interest) showed higher activation than neurotypical controls in the left superior parietal cortex during successful speech production. This effect was not specific to patients with left dorsal striatal lesions as we observed enhanced activation in the same region in some patient controls and also in more error-prone neurotypical participants. Our results strongly suggest that enhanced left superior parietal activation supports speech production in diverse challenging circumstances, including those caused by stroke damage. They add to a growing body of literature indicating how upregulation within undamaged parts of the neural systems already recruited by neurotypical adults contributes to recovery after stroke.